Some issues raised by the modification, in Spain, of the guardianship and custody measures adopted by foreign courts in the light of the Order of the Provincial Hearing of Barcelona of January 29, 2020 - Sabido Rodríguez, Mercedes (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
The presentation of a demand for modification of the custody and custody measures adopted by a foreign court raises some difficulties. In this work we will analyse those that have been highlighted by the Order of the Provincial Court of Barcelona of January 29, 2020, which resolves the appeal against the decision of instance that inadmissible the request for modification of measures adop-ted by a Moroccan court. We will address the determination of the international judicial competence of the Spanish courts, differentiating it from functional competence; as well as the problems related to the requirement or not of prior recognition of the decision whose modification is intended and, where appropriate, the procedure to follow.